Meconium ileus in the absence of cystic fibrosis. Issue 10 (October 1992) - Fakhoury, K; Durie, P R; Levison, H; Canny, G J
Abstract : Although meconium ileus in the absence of cystic fibrosis is considered a rare event, it was found that eight of 37 (21.6%) newborn infants with meconium ileus had no laboratory or clinical evidence of cystic fibrosis.